Significant Work Is About Self-Realization and Broader Purpose: Defining the Key Dimensions of Meaningful Work - Martela, Frank; Pessi, Anne B. (Frontiers in Psychology, 2018)
Research on meaningful work has proliferated in recent years, with an increasing understanding of the centrality of meaningfulness for work-related motivation, commitment, and well-being. However, ambiguity around the main construct, “meaningful work,” has hindered this progress as various researchers have used partly overlapping, partly differing conceptualizations. To bring clarity to this issue, we examine a broad range of various definitions of meaningful work and come to argue that meaningfulness in the broadest sense is about work significance as an overall evaluation of work as regards whether it is intrinsically valuable and worth doing. Furthermore, we argue that there are two key sub-dimensions to this work significance: Broader purpose as work serving some greater good or prosocial goals (the intrinsic value of work beyond the person in question). And self-realization as a sense of autonomy, authenticity and self-expression at work (the intrinsic value of work for the person in question). Previous definitions of meaningful work feature typically one or two of these elements—significance, broader purpose, self-realization –, but in the future it would be beneficial to clearly acknowledge all three elements in both definitions and operationalizations of meaningful work.